Naming, Order and Power: She Unnames Them All of Ursula & Lord of the Rings of Tolkien - O. Vahdet İşsevenler (İstanbul Hukuk Mecmuası)
One of the two points that establishes a relationship between law and literature is the legal themes in literary works, and the other is the literary character of law itself. More fundamentally, the ontological kinship between law and literature is that both construct a second world with words or names. In general, names are the mediums through which human beings construct a second world called culture. In this regard, language is a feature of the human condition. Arendt conceptualised this condition as vita activa and defined the categories of work, labour and action. This article analyzes the conceptions of power and order in two literary works by focusing on this condition of human beings called naming. Ursula’s work deals with the theme of naming, based on the claim that naming is a masculine activity that is only useful to humans. By refusing to replace names, the character who returns names manifests a form of divine violence. Tolkien’s work, on the other hand, distinguishes between correct and incorrect naming. In this conception, misnaming is to ignore the nature of the object and to name it to instrumentalize it. The correct naming, on the other hand, is not to rule the object but to take care of it as a gardener takes care of flowers. In this context, Ursula gives an anarchist, de-ordering message, and at the same time she rejects the potential of human beings to establish a legal-political order because she excludes the category of action that is only possible through names. Tolkien, on the other hand, while criticising domination and instrumental reason, also proposes a remedy that does not require a total rejection of human potential. His work, which finds its main idea in the motto “power corrupts”, makes us think that law is not necessarily an instrument of domination but, can also be an antidote to arbitrariness.